A Model of an Automated System for Assessing the Quality of Startups in the Field of Software Engineering (Global Journal of Computer Science and Technology, 2022)
Annotation- This article introduces an automated system for evaluating startups in the field of Software Engineering It outlines the system s components including database management expert assessments and project viability estimation The article also presents a conceptual database model and discusses the user interface for assessment calculations The system is designed to enhance the evaluation of Software Engineering startups and holds potential applications in various scenarios
Keywords: software engineering; startup evaluation; automated system; database management